Comparison of the efficacy of Solifenacin Succinate and Tolterodine for the treatment of overactive bladder syndrome (Northern International Medical College Journal, 2017)
Background : Overactive Bladder Syndrome(OAB) is not an uncommon problem. Although exact incidence of this disease in our country is not known but a significant number of people suffering from this disease seek treatment at the Urology department of different hospitals. At present two common antimuscarinic drug Solifenacin Succinate and Tolterodine are available in our country for the treatment of OAB.Objective : To compare the efficacy of Solifenacin Succinate and Tolterodine to treat OAB.Methodology : This hospital based randomized control trial was conducted in the Department of Urology, Dhaka Medical College Hospital, Dhaka and a private hospital from January 2009 to December 2010 to compare the efficacy of two new generation antimuscarinics, Solifenacin succinate and Tolterodine at their recommended doses for the treatment of OAB.Results : After 3 months of treatment it has clearly shown that Solifenacin is more effective in reducing OAB symptoms compared with extended release preparation of Tolterodine. This include statistically significant reduction in episodes of frequency, urgency, urge incontinence, nocturia and significant improvement of voided volume.Northern International Medical College Journal Vol.8(2) January 2017: 231-234